Record, Spread, Judge”: A Short Video Reflecting The Crisis Of Digital Morality And Media Manipulation In Modern Society - Kunanti, Nadia; Putri, Sasi Azhari Kirana; Fahmi , Muhammad (Ridwan Institute, 2025)
This paper presents a short script titled “Record, Spread, Judge”, which explores the moral and social impacts of digital media behavior. The story follows a lecturer who becomes the target of public outrage after a misleading video goes viral. The script reflects real-life issues such as how netizens are easily influenced by viral content, how media often use clickbait for views, and how these factors affect mental health, education, and family life. It emphasizes the need for critical thinking and ethical responsibility when consuming and sharing online content. By addressing these relevant and pressing concerns, the script serves as a creative yet powerful commentary on the dangers of social media manipulation and the lack of digital empathy in modern society.